ChemInform Abstract: Synthesis and Characterization of Ho3+‐Doped Strontium Titanate Downconversion Nanocrystals and Its Application in Dye‐Sensitized Solar Cells. Issue 5 (February 2015) - Li, Y. Y.; Hao, H. S.; Qin, L.; Wang, H. L.; Nie, M. Q.; Hu, Z. Q.; Gao, W. Y.; Liu, G. S.
Abstract SrTiO3:Ho3+ downconversion nanocrystals (Ho levels of 0, 0.5, 1, 3, 5, and 8 wt%) are prepared by solid state reaction of appropriate amounts of TiO2 Sr(NO3)2, Ho2O3, and NaCl as flux (Al2O3 crucible, 950 °C, 1 d) The obtained material is tested as a photoanode in dye‐sensitized solar cel (DSSC).